Aktivitas Komunikasi Toko Bakmie Feng dengan Konsumen: (Studi Kasus Mengenai Aktivitas Komunikasi yang Dilakukan Manajemen Toko Bakmie Feng Dengan Konsumen) - Naomi Ramadhenisa Hanimelya; M. Subur Drajat (UNISBA Press, 2022)
Abstract. Communication is the main thing that humans do every day. Communication activities in a business aim to attract consumers, provide information on a product to maintain the company's image. The purpose of this research is to find out the communication activities carried out by the Bakmie Feng Store with its consumers, as an effort in managing the Brand image that is carried out, the Bakmie Feng Store provides a